Language Mistakes in The Use of Public Space Media Advertisements in Ngunut Village Tulungagung Regency - Anggraini, Filisya Putri; Setyawan, Bagus Wahyu (MEDIASI, 2021)
Advertising is a tool for someone to promote the goods or places of business that they offer. From the advertisements, consumers can find out what the seller sells. From the advertisements, consumers can be interested and buy the products. The Language used in advertising is very diverse because it is to attracts the attention of consumers. This advertisements research has found errors in the use of language with the descriptive qualitative method. The data were taken from banners and signboards around the Ngunut village road, Tulungagung district. From this study, it was found that there were still errors in using the language of making the advertising media in the advertising language. The errors are punctuation, word writing, and name phrase structure errors using Indonesian and English.